2015
DOI: 10.1007/s13277-015-3771-x
|View full text |Cite
|
Sign up to set email alerts
|

Serine-arginine protein kinase 1 is associated with hepatocellular carcinoma progression and poor patient survival

Abstract: The pre-mRNA splicing regulator serine-arginine protein kinase 1 (SRPK1) promotes cancer development and various pathophysiological processes. However, the clinical relevance of SRPK1 in hepatocellular carcinoma (HCC) is not clear. This study investigates the expression and prognostic value of SRPK1 in HCC. We found that SRPK1 expression was significantly upregulated at the mRNA and protein level in all HCC cell lines or HCC tissue samples compared with the hepatic cell line or matched noncancerous tissue samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…4a). Previous studies have demonstrated that SRPK1 is highly expressed in HCC cells and tissues, and associates with poor prognosis and aggressive phenotype of HCC [25, 26]. To confirm this hypothesis, we performed qRT-PCR and Western blot analysis and found that ectopic expression of miR-1296 dramatically decreased, whereas miR-1296 knockdown increased the expressions of SRPK1 mRNA and protein in HCC cells ( P  < 0.05, respectively, Fig.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…4a). Previous studies have demonstrated that SRPK1 is highly expressed in HCC cells and tissues, and associates with poor prognosis and aggressive phenotype of HCC [25, 26]. To confirm this hypothesis, we performed qRT-PCR and Western blot analysis and found that ectopic expression of miR-1296 dramatically decreased, whereas miR-1296 knockdown increased the expressions of SRPK1 mRNA and protein in HCC cells ( P  < 0.05, respectively, Fig.…”
Section: Resultssupporting
confidence: 52%
“…Previous studies confirmed that SRPK1 predicts poor survival and promotes cell proliferation of HCC through PI3K/AKT signaling [25, 26]. Subsequently, to confirm the biological role of SRPK1 in metastasis and EMT progression, SRPK1 was knocked down by a specific siRNA in HCCLM3 cells ( P  < 0.05.…”
Section: Resultsmentioning
confidence: 76%
“…Our data showed that SRPK1 was associated with alternative splicing of CHK1 in both cancer cells and tumor tissues. Furthermore, SRPK1 had been reported to associate with hepatocellular carcinoma progression and poor patient survival [38]. Therefore, SRPK1 may mediate CHK1-S mRNA splicing through its downstream splicing factor in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The SRPK1-induced PI3K/AKT pathway interacts with miR-1296 [45] ↑SRPK1 was found in hepatocellular cancer cell lines [46] ↑SRPK1 was found in hepatocellular cancer cell lines and promoted proliferation ↓SRPK1 suppressed proliferation in vitro and growth in vivo and in vitro SRPK1 interacts with the PI3K/AKT pathway [47] Esophagus ↑SRPK1 was found in esophageal cancer cell lines and promoted proliferation ↓SRPK1 suppressed proliferation, migration, and invasion and enhanced apoptosis in vitro also suppressed tumor growth in vivo SRPK1 interacts with the TGF-β pathways [48] Pancreas ↑SRPK1 was found in pancreatic cancer cell lines ↓SRPK1 suppressed proliferation and enhanced apoptosis and sensitivity to chemotherapy in vitro SRPK1 interacts with SR proteins and regulates apoptosis [22] SRPK1 interacts with the AKT and MAPK pathways [36] Blood (Leukemia) ↓SRPK1 suppressed proliferation in vitro and tumor growth in vivo, while it enhanced cell cycle arrest, apoptosis and prolonged the survival of animal models in MLL-rearranged AML; ↓SRPK1 switched BRD4 splicing, favoring the production of its long isoform SRPK1 modulates the alternative splicing of BRD4, MYB, and MED24 [65] ↑SRPK1 was found in various myeloid and lymphoid leukemia cell lines ↓SRPK1 was cytotoxic and enhanced apoptosis in vitro SRPK1 interacts with the SR proteins and modulates the expression and splicing of MAP2Ks, VEGF, and FAS [66] ↓SRPK1 suppressed proliferation while it enhanced autophagy and apoptosis in a synergistic fashion with chemotherapy in vitro SRPK1 interacts with SR proteins and modulates the expression of MAP2Ks and VEGF and the splicing of RON [67] ↓SRPK1 suppressed proliferation and enhanced apoptosis in vitro in CML SRPK1 interacts with the PARP-caspase-3 pathway [68] Kidney ↑SRPK1 was found in renal cancer cell lines ↓SRPK1 suppressed proliferation, migration, and invasion in vitro, also tumor growth in vivo SRPK1 interacts with PI3K/AKT pathway [50] Brain (Glioma) ↑SRPK1 was found in glioma cell lines ↓SRPK1 suppressed proliferation, migration, and invasion of glioma cells in vitro while it induced resistance to chemotherapy [51] ↓SRPK1 suppressed tumor growth and apoptosis in vivo, also angiogenesis in vitro and in vivo…”
Section: ↓Srpk1 Suppressed Migration and Invasion In Vitromentioning
confidence: 95%
“…In stomach cancer, high SRPK1 was also found compared to the normal stomach histology [31,[41][42][43][44] and was associated with higher grade, stage, larger tumor size, lymph node metastases, and shorter overall survival [41,43,44]. Liver cancer was also characterized by SRPK1 overexpression, while the latter was correlated with higher stage, larger tumor size, and shorter survival [45][46][47]. In esophageal cancer, high expression of SRPK1 was associated with higher grade, stage, the capacity to metastasize, and shorter overall survival at both univariate and multivariate levels [48].…”
Section: Cancer Type (Primary Location)mentioning
confidence: 99%